2020
DOI: 10.3390/ijerph17113809
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Liver Transplant Recipients: A Retrospective Study

Abstract: Background: This study aims to investigate the quality of life and the therapeutic compliance of the patients who received a liver transplant, from a living or deceased donor, at IRCCS ISMETT in the last three years. Liver transplantation is an effective therapeutic strategy for patients with end-stage liver failure. The quality of life (QOL) of liver disease patients is placed under considerable stress due to the debilitating clinical conditions and related issues experienced in everyday life by these individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In our study, there was no statistically significant difference in BAI scores between the groups, but the fact that BAI scores in the late period group were higher than those in the early period group suggests that the level of anxiety may increase as the time after transplantation passes. Many factors such as time after liver transplantation, immunosuppressive drugs, adaptation to restrictive lifestyle rules, negative impact on quality of life, coping style with stress, and family environment may be effective in the difference between the studies in the literature [27][28][29]. In addition, the relationship between otologic symptoms and psychological symptoms in transplant patients obtained in our study should not be forgotten.…”
Section: Discussionmentioning
confidence: 74%
“…In our study, there was no statistically significant difference in BAI scores between the groups, but the fact that BAI scores in the late period group were higher than those in the early period group suggests that the level of anxiety may increase as the time after transplantation passes. Many factors such as time after liver transplantation, immunosuppressive drugs, adaptation to restrictive lifestyle rules, negative impact on quality of life, coping style with stress, and family environment may be effective in the difference between the studies in the literature [27][28][29]. In addition, the relationship between otologic symptoms and psychological symptoms in transplant patients obtained in our study should not be forgotten.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, in another report[ 49 ], the HRQoL of 82 LT recipients was retrospectively assessed, finding 94% reported high mean scores on HRQoL, the McGill Quality of Life Questionnaire, and adherence to medications. Conversely, patients with a low HRQoL reported anxiety, depression, fatigue, slowing pace, and physical limitations, suggesting that LT recipients who fail to adapt to their post-LT state experienced a decreased ability to tolerate physical symptoms and post-LT complications[ 50 ]. Other causes for lower mental health scores post-LT are the worry regarding medication side effects, hepatic disease recurrence, and other potential complications[ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Side effects from mandatory post-transplantation immunosuppressive drugs can sometimes negatively impact patients. Studies researching the effects of drugs used after transplantation identified that physical symptoms like fatigue, muscle weakness, excessive appetite increase, backache and headache, pruritis, dizziness, diarrhea and feeling thirsty were experienced (5,6). At the same time, these patients experienced several psychological and emotional symptoms like depression, irritability, fatigue and hand tremors (6).…”
Section: Introductionmentioning
confidence: 99%